The role and functions of soil in the Information and Knowledge Society - Bogdan Vasile Cioruța; Mirela Ana Coman (International Journal on Food, Agriculture and Natural Resources, 2023)
Much has been written about the soil over time, from different perspectives, however, the soil as an entity, as well as its role and functions are far from being fully recorded. In the Information and Knowledge Society, soil still has a significant role to play, in terms of its functions at the community level. We set out to make some scientific remarks and examples on these issues. Also, the soil is subjected to analysis as a cosmic-telluric-biotic product, in its gradual transition from the Hunting and Agrarian Society to the Society based on technology, information, and knowledge. What we have managed to summarize is a summum of definitions of the soil, and a conglomeration of functions, carefully nuanced and delimited, which open the way for the reader from the soil seen as a resource-support of the technosphere to the soil treated as a primary scientific concern.